SENSITIVE DETECTION OF SARS-COV-2 USING AN ENZYME-LINKED OLIGONUCLEOTIDE ASSAY - Shola David, Michael (Nazarbayev University School of Sciences and Humanities, 2022)
The rapid spread of COVID’19 has necessitated the need for the development of rapid diagnostic techniques as a strategy to contain further transmission of the virus. Aptamer-based detection assay like enzyme-linked oligonucleotide assay (ELONA) is promising as it is cheaper to run with high sensitivity and specificity. Aptamers offer a potential advantage over antibodies in the characteristics of broad modification, small size, in vitro selection, and stability under stringent conditions, which assist the creation of scalable and reliable detection. In this study, we sought to develop a simple and sensitive ELONA detection tool for SARS-CoV-2 using specific aptamers against SARS-CoV-2 RBD S protein. Screening of CoV2-RBD-1C and CoV2-RBD-4C aptamers and optimization of the assay conditions led to the development of a direct ELONA able to detect SARS-CoV-2 RBD S protein in buffer solution and spiked in 0.1% human nasal fluid with a detection limit of 2.16 ng/mL and 1.02 ng/mL, respectively. To further test the practicality of the developed assay, we successfully detected inactivated Alpha, Wuhan, and Delta variants of SARS CoV-2 with a detection limit of 3.73, 5.72, and 6.02 TCID50/mL respectively. Furthermore, we applied the two aptamers as capture and reporter elements to develop a more sensitive sandwich assay to detect the three variants of SARS-CoV-2 used in this study, and as expected a lower detection limit was obtained as follows: 2.31 TCID50/mL for Alpha variant, 1.15 TCID50/mL for Wuhan variant, and 2.96 TCID50/mL for Delta variant, which validated the high sensitivity of the sandwich assay. The sandwich ELONA was also capable of detecting both Alpha as well as Wuhan variants spiked in 0.1% human nasal fluid in a viral titer of 104 TCID50/mL. Finally, an SEM study was conducted to visualize the presence of viral particles in the Delta variant sample obtained. The results of this study have demonstrated the possibility and usefulness of our aptamer-based assay for the clinical diagnosis of SARS-COV-2
Keywords: Type of access: Embargo; SARS-CoV-2; RBD; spike protein; aptamers; ELONA; detection